Morphological changes during programmed cell death (PCD) using laser scanning confocal microscopy / Nurul Ain Mohd Noor - Mohd Noor, Nurul Ain (2012)
The purpose of this research is to observe morphological changes on MCF-7 and HCT-116 cell lines treated with aqueous extracts of M. platytyrea from Rubiaceae family. The concentrations of M. platytyrea used in this research are (0.01, 0.1, 0, 1, 10, 100, and 1000 μg/ml). From the result, apoptosis were detected in both cells. For HCT-116, the aqueous extract of M. platytyrea induced apoptosis about 10 times higher than the control. Meanwhile, in MCF-7, apoptosis was induced about 47 times higher than the control using the same extract. This further suggested that the aqueous extract of M. platytyrea was more selective to induce apoptosis in breast cancer cells compared to colon cancer cells.